Mixed Surfactants in Acetonitrile-Water Mixtures for the separation of Organic ompounds by HPLC - Abu-Shammala, Farida (Asian Journal of Chemistry, 2010)
The effect of the addition of surfactants (50 nM, i.e., above cmc) as organic modifiers into a solution containing 50% acetonitrile (+ 50% water) at neutral pH (7.0) for separating 17 organic compounds has been studied experimentally. The results have shown that the capacity factors, k´, of the organic compounds are sharply dependent on the types and the number of surfactants used. Surfactants (single, binary or ternary) have shown to provide dramatic reduction in the capacity factors of the organic compounds studied. Binary additives have lowered the capacity factor more than single additive. The use of binary mixed surfactants comprised of anionic (dioctylsulfosuccinate) (DOSS) and cationic (cetyltrimethylammonium) (CTAB) surfactants result in greater lowering in the capacity factor more than the use of other binary additives. Ternary additives lowered the capacity factor than the binary additives. A ternary mixture of surfactants from anionic (dicetylsulfosuccinate) (DOSS), cationic (cetyltrimethylammonium) (CTAB) and nonionic (poly oxyethylene) (23) dodecanol) (Brij-35) appeared to be more effective in lowering the capacity factor than the other ternary additives systems.